PERAN DINAS KEBERSIHAN DAN PERTAMANAN (DKP) DALAM MENINGKATKAN SARANA WISATA KOTA MASYARAKAT KOTA SURABAYA (STUDI KASUS PADA WISATA MANGROVE WONOREJO) - Alfizar, Fandy (JPAP: Jurnal Penelitian Administrasi Publik, 2016)
Tourism is a wide range of tourist activities and supported a variety of facilities and services provided by the public, employers, Government and Local Government. Wonorejo Mangrove Tour became one of the sights that have become icons of Surabaya citizens in the eyes of the local tourist travelers and foreign tourists. However, the actual inside Ecotourism Mangrove Wonorejo Surabaya are still many deficiencies, among others in terms of management and in terms of amenities. Associated with the condition, the author will conduct in-depth studies related to the role of manager of the parties in this case is devoted to and Sanitation Department (DKP) in developing Mangrove Wonorejo Tour as to improve tourist facilities lives in Surabaya city. The purpose of this study was to describe the role and Sanitation Department (DKP) Surabaya City Government on Mangrove Wonorejo Tour improve tourist facilities in the city of Surabaya City community. The research approach used in this study is a qualitative approach. Informants in this study is the travel manager of Mangrove Wonorejo Rungkut and surrounding communities Mangrove Wonorejo Rungkut travel. The collected data were analyzed with descriptive qualitative analysis. The results showed that the role and Sanitation Department (DKP) in Surabaya on Mangrove Wonorejo Tour in improving tourism facilities the city lives in Surabaya is just a role and focus in the cleanliness and landscaping in Wonorejo Mangrove Tour. More attention and Sanitation Department (DKP) in Surabaya to the tourist destination in this case is Mangrove tour Wonorejo Tour more emphasis on hygiene. And Sanitation Department (DKP) in Surabaya has always appealed to the manager and the local community to always keep the Mangrove Wonorejo sites. The management and the local community can then give an example of protecting the environment, especially in tourist locations mangrove Wonorejo that visitors have the awareness to jointly preserve mangrove ecosystems. Keywords: Tourism,Â Tour Facilitation City, and Sanitation Department (DKP)